-10-x=-13

Simple and best practice solution for -10-x=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10-x=-13 equation:


Simplifying
-10 + -1x = -13

Solving
-10 + -1x = -13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + -1x = -13 + 10

Combine like terms: -10 + 10 = 0
0 + -1x = -13 + 10
-1x = -13 + 10

Combine like terms: -13 + 10 = -3
-1x = -3

Divide each side by '-1'.
x = 3

Simplifying
x = 3

See similar equations:

| 9z+5-7z=59-7z | | 6x+3-1=26 | | 3(x-2)+x=7(2x+1)-3 | | (3x-2.5)-(2x-2.1)= | | 30=-26-8x | | -7h-17-6+4h=17-h | | x^4=8x^6+128x^2-16 | | 5[2x-3]=3[3x+2] | | (3c-8)-(-5c+3)= | | f^2=-44 | | 2+x=-4x+12 | | 3(2x+-5)=2(3x+-1)-13 | | 28=-9(7h+4) | | -6(5-r)=12 | | 15+-2C=7 | | 2a^2-5a=0 | | 2=-4x+5x+6 | | 4x^2=-16x+4 | | 2.3x+2=12.3x+2.8x-6 | | x+15=10-x+10 | | 3A^2-4AB+B^2=0 | | 3(2x+-5)=2(3x+-1)+7 | | 5x-12=4x+20 | | -4.5x-y=3 | | 0=96x-12x^2 | | x+1.4=1.09x | | 1862=49(p+10) | | 10r^2+20=200 | | d-2d+3=3 | | 7x-4=-11-10(6-x) | | 7x^2=8x-1 | | 10+4x+4x=42 |

Equations solver categories